Effects of external magnetic field on the solidification process in Nd–Fe–B alloy: phase-field simulation. (22nd January 2018) - Feng, Z K; Hong, Y; Wang, G; Wu, X H; Zeng, D C
Abstract: The isothermal solidification [liquid → T1 (Nd2 Fe14 B) +  α -Fe + amorphous phase] of supercooled Nd–Fe–B alloy was simulated by a phase-field method, and the effects of external magnetic field on microstructural evolution were investigated. It was demonstrated that an external magnetic field could refine grains, promote formation of texture and inhibit formation of the amorphous phase during the solidification process. Further, the demagnetization curves of various microstructures solidified under different conditions were calculated by micromagnetic simulations. It was found that the magnetic properties of Nd–Fe–B magnets could be improved by the effects of a magnetic field on solidification structures.